2012
DOI: 10.1097/wnr.0b013e3283505ac6
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of auditory distraction revealed in theta-band EEG

Abstract: Selective attention involves the exclusion of irrelevant information in order to optimize perception of a single source of sensory input; failure to do so often results in the familiar phenomenon of distraction. The term 'distraction' broadly refers to a perceptual phenomenon. In the present study we attempted to find the electrophysiological correlates of distraction using an auditory discrimination task. EEG and event-related potential responses to identical stimuli were compared under two levels of distract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
30
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 22 publications
7
30
1
Order By: Relevance
“…First, our findings are consistent with an oscillatory model of ERP generation in which the amplitude of the evoked response depends in part on phase resetting and phase alignment of EEG oscillations (e.g., Makeig et al, 2002;Jansen & Brandt, 1991). Consistent with previous work, the current results show that the amplitude of the visual P1 ERP was correlated with the cross-trial phase-locking of theta-band neural oscillations (Ponjavic-Conte et al, 2012;Gruber et al, 2005;Klimesch et al, 2004). However, phase measures did not predict all of the variance in ERP amplitude, and the correlation was only marginally significant at several recording sites.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…First, our findings are consistent with an oscillatory model of ERP generation in which the amplitude of the evoked response depends in part on phase resetting and phase alignment of EEG oscillations (e.g., Makeig et al, 2002;Jansen & Brandt, 1991). Consistent with previous work, the current results show that the amplitude of the visual P1 ERP was correlated with the cross-trial phase-locking of theta-band neural oscillations (Ponjavic-Conte et al, 2012;Gruber et al, 2005;Klimesch et al, 2004). However, phase measures did not predict all of the variance in ERP amplitude, and the correlation was only marginally significant at several recording sites.…”
Section: Discussionsupporting
confidence: 92%
“…One study compared the influence of two levels of auditory distractions during an auditory discrimination task (Ponjavic-Conte, Dowdall, Hambrook, Luczak, & Tata, 2012). Relative to a white noise sound, a continuous auditory speech in the unattended ear impaired task performance and also reduced the N1 amplitude evoked by nontarget stimuli in the attended ear.…”
Section: Introductionmentioning
confidence: 99%
“…Among EEG bands, the theta frequency, which is generated by the interplay of the glutamatergic and the Îł-aminobutyric acid (GABA)-ergic neurons [23,24], may be a suitable candidate. Documents have shown that the theta band is induced via the limbic-hippocampal-cortical feedback loop and is auditory specific [25,26,27]. Although other frequency bands exist, such as gamma rhythm, which is related to the GABA/glutamate interplay, our previous results [28] have demonstrated that the low-frequency theta band is specific to octave illusion response.…”
Section: Introductionmentioning
confidence: 84%
“…2008; Ponjavic-Conte et al. 2012). Related to the findings in these studies, it can be assumed that a measure based on the cortical response is an appropriate way to estimate the listening effort.…”
Section: Introductionmentioning
confidence: 99%